PENGARUH PENGGUNAAN SOPHIA (MINUMAN BER ALKOHOL) DAN LAMA SIMPAN YANG BERBEDA TERHADAP KUALITAS DAGING SE’I SAPI BETINA TUA (Effect of Using Sophia Use in Difeerent Storage Times on the Quality of Smoked Meat from Aged Cow Female Beef) - Fore Kehik, Agatha Feriyanti; Sipahelut, Geetruida M.; Sabtu, Bastari (JURNAL NUKLEUS PETERNAKAN, 2025)
The purpose of this study was to determine the effect of using Sophia (alcoholic beverage) use in difeerent storage times on on the quality of smoked meat from aged cow female beef. This study used 36 kg of fresh old female beef, Sophia and saltpeter. The method used was a Completely Randomized Design (CRD) 4x4 factorial pattern. The two factors applied were: the factor of giving the level of Sophia use 0% (Control), 10%, 12%, 14%. The storage time factor was 3 days, 6 days, 9 days. Each treatment was repeated 3 times to obtain 36 experimental units. The parameters in this study were pH, total bacteria and organoleptic. The data obtained were analyzed using analysis of variance (Analysis of Variance / Anova). Organoleptic data were calculated using the Non-Parametric Kruskall-Wallist test method, if there were differences, continued with the Mann-Whitney test. The results showed a significant interaction between Sophia levels and storage duration on the pH of se'i meat, where the pH decreased on the 3rd day with a level of 14% Sophia. TPC increased from 1.03 X 102 on the 3rd day to 4.09 X 102 on the 6th day but decreased from 2.15 X 102 to 1.76 with the administration of Sophia. The conclusion is that the use of Sophia levels and storage duration factors for old female se'i meat has the potential to improve the quality of pH, total plate count (TPC) and organoleptic at the level of 10%-14% during storage.